PEMANFAATAN GENOGRAM KARIR DALAM BIMBINGAN KARIR UNTUK MENINGKATKAN KEMAMPUAN PENGAMBILAN KEPUTUSAN KARIR PESERTA DIDIK - Luthvan Hilman; Dhika Chelvian Satya Benardy; Evi Winingsih; Nurul Qomariyah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Career decision-making ability refers to an individual's capacity to make career choices that align with their personal desires, talents, and interests. A genogram, a three-generational family map, can be used as a tool to assess the counselor's involvement in shaping a student's career path, as the professions of parents and grandparents can influence a child's career choice. This study aims to enhance the career decision-making skills of high school students through group counseling services utilizing the career genogram technique among participants of grade XII MIPA 5 at SMA Negeri 1 Sumberrejo, with a sample of 8 students experiencing difficulties in making career decisions. This research uses Guidance and Counseling Action Research (CAR) with two cycles. Data collection was carried out through the career decision-making skill instrument. The research findings indicate that group counseling services with career genogram media are effective in improving students' career decision-making abilities.